2009
DOI: 10.1016/j.acra.2009.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Quantitative Ultrasound Measures of the Biceps and Supraspinatus Tendons

Abstract: Rationale and Objectives-Ultrasound is a proven method for examining soft tissue structures including tendons, and recently quantitative ultrasound has become more prevalent in research settings. However, limited reliability data has been published for these new quantitative ultrasound measures. The main study objective is to quantify the reliability and measurement error of multiple quantitative ultrasound imaging protocols for the biceps and supraspinatus tendons.Materials and Methods-Two examiners captured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 19 publications
3
60
0
2
Order By: Relevance
“…72 Thus, as an evidence-based outcome measure, the sonographic assessment of cross-sectional supraspinatus tendon thickness was used because significant functional improvement may be related to structural changes of the tendon. 18,63,73 The finding of this study pointed out that not only the manual therapy intervention but also the kinesiotape intervention with exercise had no effect on tendon structure within 6 weeks. Furthermore, although the affected side, supraspinatus tendon, was a little bit thicker than the nonaffected side, no statistically differences were observed before and after the intervention or in the affected and nonaffected sides within and between groups.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…72 Thus, as an evidence-based outcome measure, the sonographic assessment of cross-sectional supraspinatus tendon thickness was used because significant functional improvement may be related to structural changes of the tendon. 18,63,73 The finding of this study pointed out that not only the manual therapy intervention but also the kinesiotape intervention with exercise had no effect on tendon structure within 6 weeks. Furthermore, although the affected side, supraspinatus tendon, was a little bit thicker than the nonaffected side, no statistically differences were observed before and after the intervention or in the affected and nonaffected sides within and between groups.…”
Section: Discussionmentioning
confidence: 77%
“…The radiologist examined anatomical structures and measured maximal supraspinatus tendon thickness with a longitudinal angle in 1 cm proximal of the lateral aspect of humerus head with GE Logiq 9 scanner (General Electric Medical Systems, Milwaukee, WI) and linear 12-MHz (10-14 MHz) probe while the participant was sitting with the hand on his/her back at the gluteal region. 18,19,62,63 In compound imaging, a 60-dB gain parameter was used. Supraspinatus tendon thickness in centimeters and any structural changes were recorded (Fig 4).…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…This reduced the variation in transducer location for the ultrasound measurements, making the procedure more reliable. 31 The protocol used to examine the structures in the shoulder was the same in both ultrasound examinations, and it was based on previously described techniques. [32][33][34] To examine the transverse image of the biceps tendon, the subject′s hand was placed on their thigh with the palm facing upward.…”
Section: Measures Of Shoulder Pathologymentioning
confidence: 99%
“…[14][15][16] Given the number of studies that have reported reliability and repeatability of the patel-lar and Achilles tendons it is surprising that few reports are available for tendons of the upper limb. Although reliability of tendon thickness for the proximal long head tendon of the biceps brachii was reported, [17] the distal biceps brachii (dBB) tendon was not studied. This tendon is particularly important as most upper limb movements are regulated through its contribution to forearm flexion and supination.…”
Section: Introductionmentioning
confidence: 99%